Complete chloroplast genome sequencing of five Salix species and its application in the phylogeny and taxonomy of the genus - Jie Zhou; Zhongyi Jiao; Jiahui Guo; Bao song Wang; Jiwei Zheng (Mitochondrial DNA. Part B. Resources, 2021)
In this study, whole chloroplast genomes of five Salix species (S. argyracea, S. dasyclados, S. eriocephala, S. integra ‘Hakuro Nishiki’, and S. suchowensis) were sequenced. These chloroplast genomes were 155 ,605, 155, 763, 155, 552, 155, 538, and 155 ,550 bp in length, harboring 131 genes (77 unigenes), 37 tRNA genes, 8 rRNA genes, and 86 mRNA genes, respectively. The genes ycf1, psaI, ycf2-2, rpoC2, rpl22, atpF, and ndhF were under positive selection among the 21 Salix species. psaI, ycf2-2, atpF, and ycf1-2 were under positive selection between the tree willow and shrub willow, and rpoC2, rpl22, and ycf1-2 were positively selected among the shrub genomes. The gene rps7 was most variable among the genomes. Phylogenetic analysis of 21 Salix species and Chosenia arbutifolia provide evidence that the cp genome data partially support the relationship with traditional taxonomic concepts in the Flora of China. This chloroplast genome elucidates Salix taxonomy and provides evidence for evolutionary research.